2004
DOI: 10.1007/s00122-004-1767-9
|View full text |Cite
|
Sign up to set email alerts
|

A genetic linkage map of microsatellite, gene-specific and morphological markers in diploid Fragaria

Abstract: Diploid Fragaria provide a potential model for genomic studies in the Rosaceae. To develop a genetic linkage map of diploid Fragaria, we scored 78 markers (68 microsatellites, one sequence-characterised amplified region, six gene-specific markers and three morphological traits) in an interspecific F2 population of 94 plants generated from a cross of F.vesca f. semperflorens x F. nubicola. Co-segregation analysis arranged 76 markers into seven discrete linkage groups covering 448 cM, with linkage group sizes ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 34 publications
3
85
0
Order By: Relevance
“…This phenomenon of distorted segregation ratios of molecular markers due to self-incompatibility has been reported in other species including Fragaria (Sargent et al, 2004), citrus (Ruiz and Asins, 2003), and Phalaris coerulescens (Bian et al, 2004). However, on LG1, just three out of the eight distorted loci mapped close to CDO89 and OSE, markers known to map in the proximity of S (http:/ /ukcrop.net/perl/ace/search/ FoggDB).…”
Section: Linkage Map Constructionsupporting
confidence: 55%
“…This phenomenon of distorted segregation ratios of molecular markers due to self-incompatibility has been reported in other species including Fragaria (Sargent et al, 2004), citrus (Ruiz and Asins, 2003), and Phalaris coerulescens (Bian et al, 2004). However, on LG1, just three out of the eight distorted loci mapped close to CDO89 and OSE, markers known to map in the proximity of S (http:/ /ukcrop.net/perl/ace/search/ FoggDB).…”
Section: Linkage Map Constructionsupporting
confidence: 55%
“…chiloensis sex chromosome is correct is our finding of the SCAR2 marker at the top of VI-A; this marker has been shown to cosegregate with the seasonal flowering locus (Albani et al 2004), which has been mapped to the top of LG 6 in the diploid FV3FN map (Sargent et al 2004).…”
Section: Sex Expressionmentioning
confidence: 85%
“…In F. chiloensis, male sterility is linked to the markers EMFn153 (at a LOD of 15.01) and EMFv160 (at a LOD of 9.73), both of which clearly map to the bottom of the homeologous LG 6 in the diploid (Sargent et al 2004). Furthermore, SCL values found for male sterility to a marker outside of the group are very weak (LOD of 1.9).…”
Section: Sex Expressionmentioning
confidence: 99%
“…The markers used for mapping are listed in Supplemental Table S1. Linkage maps were constructed as described earlier (Sargent et al, 2004). The F2 mapping population was characterized for FvTFL1 using TFL1-6FAM primers (Supplemental Table S1).…”
Section: Genotyping and Mappingmentioning
confidence: 99%
“…We also demonstrate how a 2-bp deletion in FvTFL1 changes the regulation of seasonal life cycles and leads to FvFT-dependent LD flowering. Repressor FvTFL1 Reverses the Photoperiodic Requirement for Flower Induction SFL, which causes seasonal flowering in F. vesca (Brown and Wareing, 1965;Albani et al, 2004), was initially mapped to F. vesca linkage group 6 (Sargent et al, 2004). In a recent study, association was found between perpetual flowering habit and a 2-bp deletion in the first exon of F. vesca TFL1 homolog, and the gene was roughly mapped between two markers with a physical distance of approximately 11 Mb in the same linkage group (Iwata et al, 2012).…”
mentioning
confidence: 99%